2014
DOI: 10.1002/cne.23617
|View full text |Cite
|
Sign up to set email alerts
|

Potential for cell therapy in Parkinson's disease using genetically programmed human embryonic stem cell–derived neural progenitor cells

Abstract: Neural transplantation is a promising strategy for restoring dopaminergic dysfunction and modifying disease progression in Parkinson's disease (PD). Human embryonic stem cells (hESCs) are a potential resource in this regard because of their ability to provide a virtually limitless supply of homogenous dopaminergic progenitors and neurons of appropriate lineage. The recent advances in developing robust cell culture protocols for directed differentiation of hESCs to near pure populations of ventral mesencephalic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 61 publications
0
32
0
Order By: Relevance
“…Cell therapy is thought to be a promising strategy for CNS repair over recent years. Neural stem cells (NSCs) and olfactory ensheathing cells (OECs) are two major types of cells used in a variety of CNS disease for both clinical application and animal models, including brain injury, spinal cord injury (SCI), Parkinsonian disease, and cognitive dysfunction (Srivastava et al, 2009;Ambasudhan et al, 2014;Rao et al, 2014;Wakeman et al, 2014). However, the sources of these two cells from hippocampus and olfactory bulb (OB) impede the progress of clinical application.…”
Section: Introductionmentioning
confidence: 97%
“…Cell therapy is thought to be a promising strategy for CNS repair over recent years. Neural stem cells (NSCs) and olfactory ensheathing cells (OECs) are two major types of cells used in a variety of CNS disease for both clinical application and animal models, including brain injury, spinal cord injury (SCI), Parkinsonian disease, and cognitive dysfunction (Srivastava et al, 2009;Ambasudhan et al, 2014;Rao et al, 2014;Wakeman et al, 2014). However, the sources of these two cells from hippocampus and olfactory bulb (OB) impede the progress of clinical application.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, they improve the motor signs of PD [18][19][20][21]. Some of the early studies found that the formation of tumor after embryonic stem cell transplantation is a major drawback of this technique [22,23]. Therefore, it is required to reduce the possibility of tumor formation.…”
Section: Cell Based Therapies For Pdmentioning
confidence: 99%
“…Recent advances in iPSC biology to successfully differentiate pluripotent cells into authentic A9 dopaminergic neurons and in Good Laboratory Practice manufacturing of these cells open a new avenue for cell replacement therapy (Sanchez-Danes et al , 2012). Several groups have initiated pre-clinical studies evaluating the use of either fetal, ESC or iPSC-derived dopaminergic cells (Ambasudhan et al , 2014). …”
Section: Current State Of Regenerative Stem Cell Therapiesmentioning
confidence: 99%